2017
DOI: 10.1016/j.jenvman.2017.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of settings management and protection status on recreational uses and pressures in marine protected areas

Abstract: Coastal populations and tourism are growing worldwide. Consequently outdoor recreational activity is increasing and diversifying. While Marine Protected Areas (MPAs) are valuable for mitigating anthropogenic impacts, recreational uses are rarely monitored and studied, resulting in a lack of knowledge on users' practices, motivation and impacts. Based on boat counts and interview data collected in New Caledonia, we i) explored factors affecting user practices and motivations, ii) constructed fine-scale pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Indeed, the latest human census conducted in 2019 showed that about 70% of the whole New Caledonian population was concentrated in the area of Nouméa 1 in the south-west lagoon. Several marine protected areas exist within this region (natural reserves with restrictions, Figure 1), but recreational activities related to navigation remain allowed, such as motor-boats, sail-boats, jet-skis and taxi-boats (Gonson et al, 2017). In addition, the coastal waters around Nouméa are intensively used by recreational users, such as high-speed motorized vessels and engine-free nautical activities (e.g., kitesurf, windsurf), that likely increase collision risk.…”
Section: Unexpected Threats In New Caledoniamentioning
confidence: 99%
“…Indeed, the latest human census conducted in 2019 showed that about 70% of the whole New Caledonian population was concentrated in the area of Nouméa 1 in the south-west lagoon. Several marine protected areas exist within this region (natural reserves with restrictions, Figure 1), but recreational activities related to navigation remain allowed, such as motor-boats, sail-boats, jet-skis and taxi-boats (Gonson et al, 2017). In addition, the coastal waters around Nouméa are intensively used by recreational users, such as high-speed motorized vessels and engine-free nautical activities (e.g., kitesurf, windsurf), that likely increase collision risk.…”
Section: Unexpected Threats In New Caledoniamentioning
confidence: 99%
“…By consciously integrating themselves with the natural environments, through educational and facilitation programmes, participants of outdoor sports, instructors and locals can become citizens with some environmental intervention ability. Some studies suggest that people tend to have more environmentally responsible behaviours when they feel connected to the environment (BERNS;SIMPSON, 2009;FISHER, 2002;GONSON et al, 2017;MAYER;FRANTZ, 2004;ROSZAK, 2001). Schultz (2002) defines connectedness as the way individuals include nature within their cognitive representation of self.…”
Section: Maintenance Of the Natural Environment Through Participants mentioning
confidence: 99%
“…Outdoor sports attract a wide range of participants to enjoy the natural environment and to engage in a variety of competitive and recreation pursuits. According to Gonson et al (2017), there is a growing number of participants in outdoor activities worldwide. In recent decades, people of different social and economic backgrounds have become involved in outdoor sports.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, onethird of all reef-building corals are considered to be at risk of extinction (Carpenter et al, 2008). One of the main causes of coral reef degradation over the past decades is worldwide demographic growth and socio-economic development, which are often accompanied by overfishing, sedimentation from urban development, eutrophication, marine pollution, and coral diseases (Hughes et al, 2003;Hoegh-Guldberg et al, 2007;Newton et al, 2007;Veron et al, 2009;Johnson et al, 2013;Séré et al, 2015), but also the increase of recreational users in coastal areas (Gonson et al, 2016(Gonson et al, , 2017. Anthropogenic disturbances on coral reefs make them much more susceptible to current and future climate change (Hughes et al, 2017), particularly with the increase of mass bleaching events (Spalding and Brown, 2015;Heron et al, 2016;Hughes et al, 2018) and ocean acidification (Schönberg et al, 2017;Eyre et al, 2018;Wu et al, 2018).…”
Section: Impact Of the Use Of A Teaching Toolbox In An Awareness Campmentioning
confidence: 99%
“…(B) Noell (disadvantaged school in urban neighborhood) and Thio (coastal school close to a marine reserve), (C) Boyer (socially-advantaged school in urban neighborhood) and Banian (coastal school near within a large fishing community), (D) Coula (rural school). et al, 1999), the education programs in an advantaged school (Wagner, 2008) and the regular experience with coral reef of children whose family have recreational activities linked with the lagoon (Gonson et al, 2016(Gonson et al, , 2017, allows urban schoolchildren to acquire a lot of so-called scientific knowledge (McClatchey, 2005). Children in a advantaged urban environment show some knowledge of marine biodiversity in their drawings of the sea, and more than 50% of them drew human activities (mainly with boats).…”
Section: Children's Representations Of Nature and Ecological Knowledgementioning
confidence: 99%